2018
DOI: 10.1364/oe.26.034474
|View full text |Cite
|
Sign up to set email alerts
|

Multi-color background-free coherent anti-Stokes Raman scattering microscopy using a time-lens source

Abstract: We demonstrate a multi-color background-free coherent anti-Stokes Raman scattering (CARS) imaging system, using a robust, all-fiber, low-cost, multi-wavelength timelens source. The time-lens source generates picosecond pulse trains at three different wavelengths. The first is 1064.3 nm, the second is tunable between 1052 nm and 1055 nm, and the third is tunable between 1040 nm and 1050 nm. When the time-lens source is synchronized with a mode-locked Ti:Sa laser, two of the three wavelengths are used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The existence of the nonresonant background can either distort or even saturate the resonant signal of Raman peaks, which reduces the image contrast. Qin et al [278] have recently demonstrated multi-colour background-free coherent anti-Stokes Raman scattering microscopy using an all-fibre, low-cost, multi-wavelength time lens source. A time lens, in analogy to a spatial lens, is simply a quadratic optical phase modulator in time, which can be approximated by a portion of a sinusoidal phase modulator [279281].…”
Section: Recent Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of the nonresonant background can either distort or even saturate the resonant signal of Raman peaks, which reduces the image contrast. Qin et al [278] have recently demonstrated multi-colour background-free coherent anti-Stokes Raman scattering microscopy using an all-fibre, low-cost, multi-wavelength time lens source. A time lens, in analogy to a spatial lens, is simply a quadratic optical phase modulator in time, which can be approximated by a portion of a sinusoidal phase modulator [279281].…”
Section: Recent Resultsmentioning
confidence: 99%
“…Pixel-to-pixel wavelength switching was achieved, which provided simultaneous two-colour CARS imaging with real-time nonresonant background subtraction. Qin et al [278] demonstrated the technique with an excised fresh tissue sample from a mouse ear and imaged molecular stretching vibrations at 2845 cm −1 (CH 2 ) and 2940 cm −1 (CH 3 ) and non-resonance background at = 2770 cm −1 . Figure 7a i–iii shows the process applied to the Raman peak of CH 3 stretching vibration from the mouse ear tissue sample.
Fig.
…”
Section: Recent Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBS2 (PBS102, Thorlabs) combined ARM1 and ARM2. Spatial synchronizations of two arms were achieved by using similar methods to those described in [18]. We placed a quarter-wave plate (QWP, WPQ05M-850, Thorlabs) and an EOM (EO-AM-NR-C1, Thorlabs) after PBS2.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, using near infrared (NIR) excitation wavelengths also increases the penetration depth, which is particularly significant for biomedical imaging [10][11][12]. Multiphoton microscopy (MPM) and coherent Raman scattering (CRS) microscopy are the most frequently applied nonlinear imaging technologies for biomedical microscopy [13][14][15][16][17][18]. The former mainly includes two-photon fluorescence (TPF), three-photon fluorescence (ThPF), second-harmonic generation (SHG), and third-harmonic generation (THG) microscopy.…”
Section: Introductionmentioning
confidence: 99%